2004
DOI: 10.1016/s0006-3495(04)74375-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Elastic Modulus of Porcine Articular Cartilage Determined at Two Different Levels of Tissue Organization by Indentation-Type Atomic Force Microscopy

Abstract: Cartilage stiffness was measured ex vivo at the micrometer and nanometer scales to explore structure-mechanical property relationships at smaller scales than has been done previously. A method was developed to measure the dynamic elastic modulus, |E(*)|, in compression by indentation-type atomic force microscopy (IT AFM). Spherical indenter tips (radius = approximately 2.5 microm) and sharp pyramidal tips (radius = approximately 20 nm) were employed to probe micrometer-scale and nanometer-scale response, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
387
3
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(421 citation statements)
references
References 52 publications
29
387
3
2
Order By: Relevance
“…The related elastic moduli are calculated using the Hertz model (SI Text) (23,24). Note that the determined absolute moduli values depend on the tip shape and the used fitting model; sharp tips are expected to rather probe the local mechanics of the underlying fibrous network (SI Text) (25)(26)(27). The deduced elastic moduli recorded along the follicle axis are shown as boxplots in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The related elastic moduli are calculated using the Hertz model (SI Text) (23,24). Note that the determined absolute moduli values depend on the tip shape and the used fitting model; sharp tips are expected to rather probe the local mechanics of the underlying fibrous network (SI Text) (25)(26)(27). The deduced elastic moduli recorded along the follicle axis are shown as boxplots in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is insufficient to detect local mechanical property variations of the examined tissue that reflect differences in cartilage structural organization at the molecular level. 41,42 To overcome these limitations, Stolz et al 22 proposed a novel, AFM-based approach they termed IT AFM. Their protocol enabled absolute measurements of the dynamic elastic modulus |E*| at two different length scales of tissue organization-micrometer and nanometer.…”
Section: Determining Biomechanical Properties Of Cartilage Repair Tismentioning
confidence: 99%
“…A sharp AFM tip has nominal radius of 20 nm that is smaller than an individual collagen fibril, Gene therapy in ovine articular cartilage repair A Ivkovic et al which typically measures around 50 nm. 22 Although microspherical tip is too big to detect subtle differences in orientation and amount of collagen fibrils, sharp pyramidal tip can discriminate such differences, resulting in higher stiffness values.…”
Section: Determining Biomechanical Properties Of Cartilage Repair Tismentioning
confidence: 99%
See 1 more Smart Citation
“…No studies of the mechanical properties of the interzone were found in the literature by these authors. Atomic force microscopy (AFM) has previously been used as a type of nanoindenter in order to analyse the mechanical properties of biological specimens including growth plate cartilage (Allen and Mao, 2004;Radhakrishnan et al, 2004), articular cartilage (Stolz et al, 2004) and single cells (Rotsch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%